Pioneer Pannist Dies - Unknown (Trinidad Guardian)
Lennox "Ranger" Glean died at the Port-of-Spain General Hospital nine days after being honoured as one of the 25 pannist termed ‘The Panguard”. Glean was honoured for his ambassadorial work as a member of the first National Steelband, which went on tour in 1960 to promote pan music on the UK/Europe.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Glean, Lennox 'Ranger'; Musicians -- Trinidad and Tobago